2020
DOI: 10.1073/pnas.1922342117
|View full text |Cite
|
Sign up to set email alerts
|

ATP13A2-mediated endo-lysosomal polyamine export counters mitochondrial oxidative stress

Abstract: Recessive loss-of-function mutations in ATP13A2 (PARK9) are associated with a spectrum of neurodegenerative disorders, including Parkinson’s disease (PD). We recently revealed that the late endo-lysosomal transporter ATP13A2 pumps polyamines like spermine into the cytosol, whereas ATP13A2 dysfunction causes lysosomal polyamine accumulation and rupture. Here, we investigate how ATP13A2 provides protection against mitochondrial toxins such as rotenone, an environmental PD risk factor. Rotenone promoted mitochond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 77 publications
0
45
0
Order By: Relevance
“…ATP13A2 knockdown induces a stress response after exposure to rotenone. Studies in C. elegans identified a conserved cell-protective pathway that alleviates mitochondrial oxidative stress via ATP13A2-mediated lysosomal spermine export [ 38 ].…”
Section: Studies With Nematode C Elegans Brougmentioning
confidence: 99%
“…ATP13A2 knockdown induces a stress response after exposure to rotenone. Studies in C. elegans identified a conserved cell-protective pathway that alleviates mitochondrial oxidative stress via ATP13A2-mediated lysosomal spermine export [ 38 ].…”
Section: Studies With Nematode C Elegans Brougmentioning
confidence: 99%
“…ATP13A2 has also been suggested to regulate multiple cellular functions related to lysosomes, including heavy metal homeostasis and mitochondrial homeostasis ( 15 , 122 ). For example, a recent study using SH-SY5Y cells, patient-derived fibroblasts and the nematode C. elegans has identified a conserved cell protective pathway that counters mitochondrial oxidative stress via ATP13A2-mediated lysosomal spermine export ( 123 ).…”
Section: Atp13a2: a Unique Cation Transporter On Lysosomesmentioning
confidence: 99%
“…Polyamines (putrescine, spermidine, and SPM) are involved in many cellular processes, including cell proliferation and differentiation, modulation of ion channels and receptors, and regulation of gene transcription and translation [ 33 ]. SPM is an antioxidant under physiological conditions [ 34 ], and we recently showed that ATP13A2-mediated SPM transport counteracts mitochondrial oxidative stress [ 35 ]. However, at high concentration, SPM exerts toxic effects, possibly due to lysosomal accumulation and lysosomal-dependent cell death [ 32 ].…”
Section: Introductionmentioning
confidence: 99%